Hubungan Kerja Lembaga Kemasyarakatan Dengan Pemerintah Kelurahan Pada Pemerintah Daerah Kota Pekanbaru - Rauf, Rahyunir (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2016)
Community Institution is one of the civil organization under the authority of village level governance, also acknowledged and under supervision of government. Indonesian legislation has given chance to society to form community institution. Act number 23/2014 on Local Government and Act number 6/2014 on Village laid foundation for society to form village level community institution based on their need. In reality, those community institution like Rukun Tetangga (RT), Rukun Warga (RW), Lembaga Pemberdayaan Masyarakat Kelurahan (LPMK), Pemberdayaan Kesejahteraan Keluarga (PKK), Karang Taruna, etc., have been an integral part in helping governmentâs task, especially the task of head of urban village related to services on governance, development, and civil matters. Civil institution in urban village has shown its benefit and function in government, especially city government. Act number 5/1974 doesnât mention about RT and RK/RW, but that does not means those institutions donât have their reason for existence (raison dieter). RT and RK/RK can be formed based on Mayorâs Order as implementation of mayorâs function on Community Administrator. As Community Administrator Mayor can form act on forming and regulating community institution in its area which in turn can help city government fulfill its communityâs participation, thus communityâs aspiration can be included in governmentâs action and further enlarge social participation. Even though it is known that some city is regulates and empowers its community institutions, it is advised that other city has to start, so it wonât be too far behind, because community institutionâs benefit and function have been proven. Working relation between community institution and urban village is deep.